The impact of trust, risk and disaster exposure on microinsurance demand: Results of a DCE analysis in Cambodia - Oliver Fiala; Danny Wende (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2016)
Natural disasters are increasing in frequency and intensity and have devastating impacts on individuals, both humanitarian and economic, particularly in developing countries. Microinsurance is seen as one promising instrument of disaster risk management, however the level of demand for respective projects remains low. Using behavioural games and a discrete choice experiment, this paper analyses the demand for hypothetical microinsurance products in rural Cambodia and contributes significant household level evidence to the current research. A general preference for microinsurance can be found, with demand significantly affected by price, provider, requirements for prevention and combinations with credit. Furthermore, financial literacy, risk aversion, levels of trust and previous disaster experience impact the individual demand for flood insurance in rural Cambodia.
urn:nbn:de:bsz:14-qucosa-203561
Keywords: Q10; Q50; Q54; O10; C25; 330; microinsurance; trust; risk; discrete choice experiment; Cambodia